Virtual/augmented reality for joint attention skills improvement in autism spectrum disorder: a systematic review. - Yazdanian, Hassan; Vakili, AmirMohammad; Soltani, Ariana; Bagheri Rekhne, Zohre; Zareii, Sajjad; Zarifian, Talieh (International Journal of Developmental Disabilities, 2025)
Deficits in joint attention (JA) are among the earliest hallmarks of autism spectrum disorder (ASD) and are targeted in early intervention programs. Virtual reality (VR) and augmented reality (AR) are emerging technologies that have attracted the interest of scientists conducting research in the ASD field in recent years. Despite the critical role of JA skills in the development of social-communication skills, only a few studies have targeted these skills using VR/AR-based interventions for individuals with autism. This systematic literature review is the first to present the state of the art in clinical applications of VR/AR-based interventions for improving JA skills in individuals with ASD. Seven peer-reviewed articles were analyzed to clarify the experimental effect of VR/AR applications on JA skills and, consequently, on social-communications skills. According to the analysis, positive results have been reported in all but one study. However, it was revealed that there was no consensus on the JA measures employed in the studies, making it difficult to compare results and draw definite conclusions about the clinical benefits of VR/AR. Due to the importance of JA, it is highly recommended that further clinical trials be conducted on the use of VR/AR-based interventions to enrich the literature on this subject.